Digital Leadership in Higher Education: A Bibliometric Mapping of Empirical Research (2015–2025) - Maurits Sahata Sipayung (Jurnal Ilmu Sosial, Manajemen, Akuntansi dan Bisnis, 2026)
Digital leadership has emerged as a strategic capability that enables higher education institutions to navigate digital transformation, technological disruption, and sustainability challenges. Despite the growing body of literature, the intellectual structure and thematic evolution of digital leadership research remain fragmented. This study aims to systematically map the intellectual landscape, research trends, and emerging themes of empirical studies on digital leadership in higher education through a bibliometric approach. Data were retrieved from the Dimensions database, yielding 233 publications published between 2015 and 2025. After applying predefined inclusion and exclusion criteria—restricting the dataset to English-language empirical studies while excluding review articles, conceptual papers, and previous bibliometric studies—a final corpus of 203 publications was analyzed. Bibliometric analysis was conducted using VOSviewer, incorporating publication trend analysis, co-authorship analysis, citation and source analysis, bibliographic coupling, and keyword co-occurrence analysis. The findings demonstrate a substantial increase in scholarly output after 2021, reflecting the growing importance of digital leadership within higher education research. Keyword co-occurrence analysis identifies five major research themes: (1) digital leadership and leadership practices, (2) digital competence and individual capabilities, (3) higher education systems, educational technology, and student outcomes, (4) organizational management, performance, and sustainability, and (5) artificial intelligence, crisis management, and strategic adaptation. Citation and collaboration analyses further reveal a globally distributed but conceptually fragmented research landscape characterized by limited international collaboration and uneven knowledge integration. By linking these thematic developments to the education-related Sustainable Development Goals (SDGs), particularly SDG 4 (Quality Education), SDG 9 (Industry, Innovation and Infrastructure), SDG 16 (Peace, Justice and Strong Institutions), and SDG 17 (Partnerships for the Goals), this study demonstrates the strategic role of digital leadership in advancing sustainable higher education governance. Furthermore, the study proposes a structured future research agenda and a set of research propositions to encourage more integrative, interdisciplinary, and outcome-oriented investigations. Overall, this study enriches the understanding of digital leadership by providing a comprehensive bibliometric synthesis that serves as a valuable reference for researchers, policymakers, and higher education leaders seeking to strengthen institutional transformation and sustainability in the digital era